SERS Microspectroscopy of Biomolecules on Dried Ag Colloidal Drops. Issue 5 (11th July 2012) - Šimáková Šimáková, P. P.; Procházka Procházka, M. M.; Kočišová Kočišová, E. E.
Abstract : We report the application of dried Ag hydroxylamine-reduced colloidal drops to surface-enhanced (resonance) Raman scattering (SE(R)RS) study of biomolecules using Raman microspectroscopy. 5, 10, 15, 20-tetrakis(1-methyl-4-pyridyl)porphyrin (TMPyP), amino acid tryptophan, and phospholipid 1, 2-distearoyl- sn -glycero-3-phosphocholine (DSPC) served as testing biomolecules. Ag colloid/biomolecule drop dried on glass support forms a ring in the edge part of the drop in which almost all nanoparticles are clustered. This specific drying process promotes adsorption of the studied biomolecules in highly enhancing sites ("hot spots") as well as concentrates them in the ring. We were able to obtain SE(R)RS spectra from the ring that cannot be acquired directly from Ag colloidal solutions (SERRS spectrum of1 × 10 − 10 M TMPyP by 1 s accumulation time, SERS spectrum of2 × 10 − 7 M DSPC). Despite the spectral irreproducibility and problems with spurious bands in some cases, SERS microspectroscopy of studied biomolecules using dried Ag colloid/adsorbate systems improves SERS applicability and sensitivity in comparison to measurements directly from Ag colloidal solution.